Laser powder bed fusion of an engineering intermetallic TiAl alloy. (March 2021) - Schimbäck, D.; Braun, J.; Leichtfried, G.; Clemens, H.; Mayer, S.
Abstract: The 4th generation of intermetallic γ-TiAl based alloys, the so-called TNM alloy with its nominal composition of Ti-43.5Al-4Nb-1Mo-0.1B (in at.%), gained attention especially as high temperature lightweight structural materials. The scope of this study is to investigate the processability of a TNM-based powder with an Al content of 45 at.% by laser powder bed fusion, characterize the microstructural features and develop a tailored heat treatment for the as-built material to adjust a microstructure with balanced mechanical properties. The slightly increased Al content was chosen to counteract an Al loss during the process. Therefore, the chemistry of the powder was investigated after each building job, especially in terms of Al evaporation and O impurities. Based on an extensive parameter study with different preheating temperatures of the base plate, crack-free samples with relative densities of 99.9% were built. It could be shown that the process parameters have a direct influence on the microstructure in terms of phase composition, grain size, and lamellar spacing. The results of the post-processing heat treatment study enable the definition of parameters for adjusting an isotropic nearly lamellar γ or a fully lamellar microstructure, which corresponds to the respective microstructure obtained using conventional processing routes. Graphical abstract: Unlabelled Image Highlights: An extensive process parameter adaptation enabled the fabrication of fully dense parts of an γ-TiAl based alloy by LPB-F. A relationship between the introduced energy and the appearance of the microstructure was elaborated. A tailor-made two-step heat treatment was developed in order to adjust a creep resistant microstructure.